Der Einfluss von Flexibilisierungsprozessen auf industrielle Produktionsstrukturen am Beispiel der chemischen Industrie - Bathelt, Harald (ERDKUNDE, 1995)
Due to the structural changes of the Fordist crisis, flexible technologies and flexible forms of labor organization have gained considerable importance within the industrial production sphere. This article aims to draw conclusions about the directions, options, risks and spatial effects of flexibility processes in industrial production. Empirical evidence will focus on the chemical industry. The use of flexible machinery enables firms to continuously adjust their products to meet changing demand conditions, such as increased market segmentation and uncertainty. Despite the widely recognized advantages of flexible technologies, adaptation rates within the industrial sectors are not as high as is frequently assumed. The implementation of flexible machinery is obviously not the only way to react to changing consumption patterns and coordination mechanisms. Neither does a transition from Fordist to flexible machinery guarantee long-term competitiveness. The implementation of flexible machinery seems especially efficient if it occurs in conjunction with consistent changes in the organization of labor, such as with functional flexibility. There is, however, no clear link between the concepts of flexible technology and flexible labor. Through a combination of different sets of flexible machinery and a flexible organization of labor, one can, nonetheless, derive specific scenarios of flexibility. Two of these scenarios are analyzed more closely in this article: flexible specialization and dynamic flexibility. The scenario of flexible specialization is based on the dominance of economies of scope and results in an industrial structure which is characterized by networks of vertically-disintegrated small and medium-sized firms. In contrast, the scenario of dynamic flexibility is built upon a combination of economies of scope and scale which leads to flexible mass production within vertically-integrated large firms. Both scenarios are closely related to specific demand structures. They are complementary in that they can take place at the same time within different market segments. The scenarios of flexible specialization and dynamic flexibility might, despite their contrasting organizational effects, lead to a similar spatial structure of economic activities which is characterized by a tendency towards industrial agglomeration. Spatial proximity might gain importance as a factor within location decisions and the establishment of interfirm linkages. The applicability of both scenarios is, however, limited and spatial outcomes have not yet been thoroughly analyzed. Furthermore, these scenarios will not fully replace traditional forms of production, such as Fordist mass production. The changes within the technological and organizational structures of industrial firms are not deterministic. Changes within the labor and production processes do not always overcome the rigidities of the Fordist production structure. Equally, flexible forms of industrial organization are not merely features of Postfordism. Often, they have already been present within the Fordist era. There is no simple dualism between Fordism (rigidity) and Postfordism (flexibility). In addition, flexibility has become a popular term to describe a variety of different and sometimes contradictory changes. Neither has the concept of flexibility been clearly defined, nor have the links between flexibility and proximity been clarified. Furthermore, empirical evidence about the significance and stability of flexible forms of industrial organization is biased, because most studies tend to concentrate on a limited number of industrial sectors and regions. These and other shortcomings indicate that industrial development will not follow a single trajectory towards flexibility. Industrial change is, and will remain, more complex than is frequently assumed. The production structure of a potential Postfordist regime of accumulation and mode of regulation is not yet clear.